COLD CHAIN LOGISTICS AND THE PERFORMANCE OF FRESH PRODUCE FIRMS IN NAIROBI CITY COUNTY, KENYA - Lipwop, Maureen Chepchirchir; Achuora, John (International Research Journal Publishers, 2021)
The study sought to establish the influence of cold chain logistics on the performance of fresh produce firms in Nairobi City County, Kenya. Specifically, the study intended to determine the influence of cold transportation mode, cold material handling, cold storage and cold information management systems on the performance of fresh produce firms. The study adopted a descriptive research design and a census survey was done on 103 fresh produce firms. The unit of analysis for this study was the fresh produce firms in Nairobi County while the unit of observation was the heads of Supply Chain Management (SCM). A structured questionnaire was used to collect primary data from the respondents. Descriptive statistics were used to describe and summarize data with the help of SPSS. Further, Pearson Correlation was used to test the assumptions of the regression model and multiple regression was used to test the study hypothesized model. The study concludes that cold transportation mode has a positive and significant effect on the performance of fresh produce firms and cold material handling has a positive and significant effect on the performance of fresh produce firms. It also concluded that cold storage facility has a positive and significant effect on the performance of fresh produce firms and that information management system has a positive and significant effect on the performance of fresh produce firms. The study recommends that the management of the fresh produce firms should minimize paper work and maximize usage of information management systems to facilitate supply chain management and to increase their customer service and profitability levels. Also, Adoption of technology in managing information will help the firms improve their efficiency and improve product quality; this will help companies improve their performance.
Keywords: Cold transportation mode; Cold material handling; Performance